1984
DOI: 10.1002/clc.4960071106
|View full text |Cite
|
Sign up to set email alerts
|

Systolic and diastolic time intervals during spontaneous angina

Abstract: Summary:In 5 patients who suffered spontaneous angina during cardiac catheterization, aortic pressure and electrocardiographic lead (V,) were recorded at rest, at the onset of anginal pain, 5 and 10 min after 0.6 mg sublingual nitroglycerin (NTG). Heart rate, systemic arterial pressure, systolic, and diastolic time intervals were measured. Heart rate and systemic arterial pressure rose significantly immediately after the onset of angina and declined progressively within 10 min from NTG administration. Preeject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Systole (heart contraction) and diastole (heart relaxation), apart from heartbeat which primarily reflects the electrical activity of the heart, are fundamental mechanical cardiac activities. In addition to heartbeat interval (RRI), the systole time interval (STI) and diastole time interval (DTI) are also potentially applicable for examining cardiovascular conditions, as evidenced by a couple of publications [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Systole (heart contraction) and diastole (heart relaxation), apart from heartbeat which primarily reflects the electrical activity of the heart, are fundamental mechanical cardiac activities. In addition to heartbeat interval (RRI), the systole time interval (STI) and diastole time interval (DTI) are also potentially applicable for examining cardiovascular conditions, as evidenced by a couple of publications [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…of DP was also found in spontaneous angina [6], dilated cardiomyopathy [7], and exercise-induced increased pulmonary artery pressure [8]. In addition to these wellstudied cardiac electrical and mechanical time intervals, there is yet another time interval characterizing the delay between the onset of the electrical activation of the ventricle and the onset of its contraction-the electro-mechanical delay (EMD) [9], [10].…”
mentioning
confidence: 96%
“…However, few data are available regarding its effects on cardiomechanical events. A transient paradoxical splitting of the second heart sound may oc cur during angina, suggesting a prolongation of left ventricular contraction related to asyn ergy [8], Furthermore, it has been observed that during spontaneous angina, accompa-nied by an increase in heart rate and blood pressure, the electromechanical systole is prolonged; this leads to a decrease in dia stolic perfusion time which, in turn, could be responsible for a self-maintaining worsening of ischemia [9], The effects of autonomic mechanisms and particularly of increased vagal tone on time intervals is not yet com pletely understood. The present study was undertaken to determine the relative effects on electromechanical events and electrocar diographic changes of acute episodes of tran sient myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%